Pengaruh Brand Image, Brand Awareness, Dan Brand Loyalty Terhadap Purchase Decision Produk Smartphone Iphone 15 (Studi Pada Konsumen Iphone 15 Di Kota Malang) - Cahyani, Berliana Regita; Farida, Eka; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The rapid development of communication technology has driven increasing public demand for smartphone, including premium products such as the iPhone 15. In the midst of competition in the smartphone industry, a product’s success in attracting consumer interest depends not only on the quality of its technology, but also on the strength of its brand image, brand awareness, and brand loyalty from its consumers. This research aims to analyze the effect of brand image, brand awareness, and brand loyalty on purchase decisions for iPhone 15 smartphone products in Malang City. The method used in this research is quantitative with an explanatory research approach. Data obtained through distributing questionnaires to 80 respondents who are iPhone 15 consumers in Malang City. The technique used is multiple linear regression analysis with the help of SPSS software. The results showed that both individually and simultaneously, the variables brand image, brand awareness, and brand loyalty had a positive and significant effect on the purchase decision of the iPhone 15 smartphone. These findings indicate that the company's efforts to build a strong brand image, increase brand awareness, and maintain brand loyalty can encourage the purchase decision of iPhone 15 smartphone products. Keywords : Brand Image, Brand Awareness, Brand Loyalty, Purchase Decision.